Debate: Towards a Cohesive and Contextualised Response: When is it necessary to distinguish between forced labour, trafficking in persons and slavery? - Paavilainen, Marja (Anti-Trafficking Review, 2015)
In my view, the answer to the debate question of whether it is necessary to distinguish between forced labour, trafficking and slavery depends on the context. Therefore the focus should instead be on identifying when it is necessary to distinguish and when it is not required. Furthermore, an essential follow-up is the question of how we can prevent and address these different forms of coercion in a coherent manner.